The Effects of Hot Isostatic Pressing Ti–6Al–4V Alloy and Its Susceptibility to Hydrogen - Lulu-Bitton, Noa; Navi, Nissim U; Haroush, Shlomo; Sabatani, Eyal; Kostirya, Natalie; Tiferet, Eitan; Ganor, Yaron I; Omesi, Ofer; Agronov, Gennadi; Eliaz, Noam (Materials, 2024)
The effects of the secondary processes of Hot Isostatic Pressing (HIP) at 920 °C and Heat Treatment (HT) at 1000 °C of Electron Beam-Melted (EBM) Ti–6Al–4V alloy on the microstructure and hydrogen embrittlement (HE) after electrochemical hydrogen charging (EC) were investigated. Comprehensive characterization, including microstructural analysis, X-ray diffraction (XRD), thermal desorption analysis, and mechanical testing, was conducted. After HIP, the β-phase morphology changed from discontinuous Widmanstätten to a more continuous structure, 10 times and ~1.5 times larger in length and width, respectively. Following HT, the β-phase morphology changed to a continuous “web-like” structure, ~4.5 times larger in width. Despite similar mechanical behavior in their non-hydrogenated state, the post-treated alloys exhibit increased susceptibility to HE due to enhanced hydrogen penetration into the bulk. It is shown that hydrogen content in the samples’ bulk is inversely dependent on surface hydride content. It is therefore concluded that the formed hydride surface layer is crucial for inhibiting further hydrogen penetration and adsorption into the bulk and thus for reducing HE susceptibility. The lack of a hydride surface layer in the samples subject to HIP and HT highlights the importance of choosing secondary treatment process parameters that will not increase the continuous β-phase morphology of EBM Ti–6Al–4V alloys in applications that involve electrochemical hydrogen environments.